Racial Attitudes: Differences in Racial Attitudes of People Attending Multiracial and Uniracial Congregations - Yancey, George (Research in the social scientific study of religion, 2002)
It has been suggested that interracial contact alters racial attitudes. Preliminary research indicates that interracial contact appears to be powerful in religious institutions. This paper examines whether attendees of multiracial religious institutions have different racial attitudes than other individuals. Regression analysis with data from the Lilly Survey of Attitude and Friendships (LSAF) examines racial, political, social distance and stereotypes, attitudinal differences between members who attend multiracial churches and other Americans. Except for stereotyping, European-Americans who are racial minorities in their churches have different racial attitudes than other European-Americans. European-Americans attending multiracial churches exhibit lower levels of social distance than other European-Americans. Few significant differences are found for racial minorities. This research indicates that racial integration in religious institutions has a stronger association with racial attitudes for majority-group members than for racial minorities.